Teaching the Statement of Changes in Financial Position: An Empirical Study. - Pratt, Jamie; Chrisman, Heidi Hadlich (The Accounting Review, 1982)
ABSTRACT: This classroom laboratory study compares the effects of two methods of teaching the Statement of Changes in Financial Position and two homework assignment strategies on student performance, time spent, and attitudes. The results indicate that students exposed to the direct teaching method scored higher on objective examination questions, spent more time on homework problems and examination problems, and perceived greater levels of understanding than students exposed to the add-back teaching method. Also, students assigned cash-basis homework problems showed higher levels of satisfaction with their instructor than students assigned working capital-basis homework problems. No interaction effects were significant.